High Lipoprotein (a) Levels in Chronic Hemodialysis Patients are Closely Related to the Acute Phase Reaction - Kario, Kazuomi; Matsuo, Takefumi; Kobayashi, Hiroko; Matsuo, Miyako; Asada, Reiko; Koide, Masanobu (Thrombosis and Haemostasis, 1995)
To study the mechanism underlying the high lipoprotein (a) [Lp(a)] level in uremic patients on chronic hemodialysis, we investigated the levels of Lp(a), acute phase reactants (C-reactive protein and sialic acid), and interleukin-6 (IL-6) in 54 dialysis patients. The mean [95% Cl] Lp(a) level was increased in the hemodialysis patients compared with the 30 controls (30 [25-36] vs. 18 [14-23] mg/dl, p <0.005). Among dialysis patients, 46% had an Lp(a) level >30 mg/dl, which was significantly higher than the percentage in the control group (17%). The levels of C-reactive protein, sialic acid, and IL-6 were also increased in dialysis subjects compared with controls (200 [134-299] vs. 37 [24-58] μg/dl, p <0.0001; 63 [59-66] vs. 54 [52-56] mg/dl, p <0.002; and 9.2 [7.8-11] vs. 5.5 [5.0-6.1]pg/ml, p <0.0005, respectively). The Lp(a) level was positively correlated with that of C-reactive protein (r = 0.415, p <0.002), sialic acid (r = 0.426, p <0.002), and IL-6 (r = 0.298, p<0.05) in the hemodialysis patients, but not in the controls or non-dialysis uremic patients. The Lp(a) level in the dialysis patients was also positively correlated with activation markers of coagulation (thrombin-antithrombin III complex and plasmin-α2-plasmin inhibitor complex, p <0.005). These results indicate that the Lp(a) level is closely related to the acute phase reaction and hypercoagulability in chronic hemodialysis patients.